Field-Triage, Hospital-Triage and Triage-Assessment: A Literature Review of the Current Phases of Adult Trauma Triage. Issue 6 (June 2021) - Morris, Rachel S.; Karam, Basil S.; Murphy, Patrick B.; Jenkins, Peter; Milia, David J.; Hemmila, Mark R.; Haines, Krista L.; Puzio, Thaddeus J.; de Moya, Marc A.; Tignanelli, Christopher J.
Abstract : ABSTRACT: Despite major improvements in the United States trauma system over the past two decades, prehospital trauma triage is a significant challenge. Undertriage is associated with increased mortality, and overtriage results in significant resource overuse. The American College of Surgeons Committee on Trauma benchmarks for undertriage and overtriage are not being met. Many barriers to appropriate field triage exist, including lack of a formal definition for major trauma, absence of a simple and widely applicable triage mode, and emergency medical service adherence to triage protocols. Modern trauma triage systems should ideally be based on the need for intervention rather than injury severity. Future studies should focus on identifying the ideal definition for major trauma and creating triage models that can be easily deployed. This narrative review article presents challenges and potential solutions for prehospital trauma triage.